Women's health literacy and the complex decision‐making process to use complementary medicine products in pregnancy and lactation - Larisa A. J. Barnes; Lesley Barclay; Kirsten McCaffery; Parisa Aslani (Wiley, 2019)
Abstract Background Little is known about women's decision‐making processes regarding using complementary medicine products (CMPs) during pregnancy or lactation. Objectives To explore the decision‐making processes of women choosing to use CMPs in pregnancy and lactation; and to investigate how women's health literacy influences their decisions. Design, setting and participants In‐depth interviews and focus group discussions were held with twenty‐five pregnant and/or breastfeeding women. Data were analysed using thematic analysis. Results Key to women's decision making was the desire to establish a CMPs safety and to receive information from a trustworthy source, preferably their most trusted health‐care practitioner. Women wanted positive therapeutic relationships with health‐care practitioners and to be highly involved in the decisions they made for the health of themselves and their children. Two overarching components of the decision‐making process were identified: (a) women's information needs and (b) a preference for CMP use. Women collated and assessed information from other health‐care practitioners, other mothers and published research during their decision‐making processes. They showed a strong preference for CMP use to support their pregnancy and breastfeeding health, and that of their unborn and breastfeeding babies. Discussion and Conclusions Complex decision‐making processes to use CMPs in pregnancy and lactation were identified. The participants showed high levels of communicative and critical health literacy skills in their decision‐making processes. These skills supported women's complex decision‐making processes.